Evaluating older persons’ perceptions on their quality of life in an old people’s institution: a Zimbabwean case study - Hungwe, Chipo (Sage publications, 2016)
This study evaluates perceptions on the quality of life of older adults and the extent to which they practiced self-determination in an institution. Participant observation, in-depth interviews, and life histories are used to study 16 older adults and 4 officials who are purposively selected and studied over 2.5 months between July and September 2002. Data are analyzed using the Miles and Huberman approach. Findings reveal that the ability to affect decisions pertaining to one’s care positively affects that individual’s perception of institutional life. The typical life course of an older male is also discussed. Older adults perceive their quality of life as negative and decreasing because they have little choice on their care and quality of life. The institution is affected by many adverse conditions in a socioeconomic environment, such as inflation at the rate of 4000% per annum, dwindling donor support, little government support, and negative attitudes of officials at Rubatsiro.